2006
DOI: 10.1183/09031936.00128505
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between asthma control and health status: the GOAL study

Abstract: The present study examined the association between guideline-derived asthma control and health-related quality of life, assessed using the Asthma Quality of Life Questionnaire (AQLQ), in patients with uncontrolled asthma whose treatment was directed towards achieving the highest possible level of control.The present randomised, double-blind, parallel-group study compared the efficacy of fluticasone propionate (FP) and salmeterol/fluticasone propionate combination (SFC) in achieving two composite, guideline-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
2
14

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 16 publications
6
108
2
14
Order By: Relevance
“…AQLQ scores improved throughout the study, and the overall score for all groups and strata approached the value of 6, suggesting that asthma no longer had a significant impact on quality of life. 4,10 Further analysis has revealed statistically significant differences between AQLQ scores in Totally Controlled, Well Controlled and Not Well Controlled patients, suggesting that the differences in these control definitions are perceptible to patients. 10 The differences between treatments were more pronounced in Strata 2 and 3 compared with Stratum 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AQLQ scores improved throughout the study, and the overall score for all groups and strata approached the value of 6, suggesting that asthma no longer had a significant impact on quality of life. 4,10 Further analysis has revealed statistically significant differences between AQLQ scores in Totally Controlled, Well Controlled and Not Well Controlled patients, suggesting that the differences in these control definitions are perceptible to patients. 10 The differences between treatments were more pronounced in Strata 2 and 3 compared with Stratum 1.…”
Section: Discussionmentioning
confidence: 99%
“…4,10 Further analysis has revealed statistically significant differences between AQLQ scores in Totally Controlled, Well Controlled and Not Well Controlled patients, suggesting that the differences in these control definitions are perceptible to patients. 10 The differences between treatments were more pronounced in Strata 2 and 3 compared with Stratum 1. This may be due to patients in Strata 2 and 3 experiencing nearmaximal improvements from the ICS doses used prior to screening.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that both MDIs and DPIs are adequate for COPD, even severe COPD. Subgroup analysis of the GOAL21 and TORCH22 study results showed that the combination of fluticasone and salmeterol, which are DPIs, was effective for both asthma in elderly patients and COPD. It is important to select ICS devices for ACOS patients on the basis of the inhalation technique, device type, and patient compliance.…”
Section: Treatment Of Syndromic Diagnosis Of Acosmentioning
confidence: 99%
“…6 Total control is the aim. There are a number of important conclusions that can be drawn from this study.…”
Section: Is Asthma Control Achievable?mentioning
confidence: 99%